Calibration of a simplified macro-model for infilled frames with openings. Issue 2 (January 2018) - Furtado, André; Rodrigues, Hugo; Arêde, António
During the last years, some experimental efforts were conducted in order to evaluate the in-plane cyclic behaviour of infilled reinforced concrete frames considering and not openings. From the experiments, it was observed that the openings reduced infill panels' stiffness, strength and energy dissipation capacity. In the literature, there are different numerical approaches to predict the infill panels expected behaviour with and/or without openings when subjected to in-plane demands. The experimental data are of full importance to calibrate the numerical models and evaluate their accuracy. A good calibration of the numerical models could result on a better and accurate safety assessment of the existing buildings and designing of the new ones. The main aim of this article is to evaluate the capacity of a simplified double strut model to represent the cyclic behaviour of infilled reinforced concrete frames with and without openings using the software OpenSees. The five infilled reinforced concrete frames tested by different authors and with different configurations will be simulated. Details from each specimen modelling will be provided along the article, and the accuracy of this numerical modelling approach will be evaluated in terms of force–displacement hysteretic curves. Additionally, a state-of-art review regarding the in-plane tests will be presented containing the main characteristics of the specimens and conclusions performed by each author.